Site suitability and the analytic hierarchy process: How GIS analysis can improve the competitive advantage of the Jamaican coffee industry. (March 2015) - Mighty, Mario A.
Abstract: This paper presents a site suitability model for growing coffee in the island of Jamaica and how it can be used to assist the development of the Jamaican coffee industry as it seeks to regain the presence it once had in the specialty coffee market. Home to the Jamaica Blue Mountain coffee – one of the world's most exotic and expensive coffees, the industry has struggled in face of increased competition in the specialty coffee market and increasing costs of production. This decline in competitive advantage has forced stakeholders to seek innovative means to remain viable. This suitability model integrated the perspectives of local coffee stakeholders using the analytic hierarchy process to determine the weights for the biophysical and infrastructure criteria used in the suitability analysis. The results indicated that the most suitable locations for growing coffee in the island were in the mountainous core of central and eastern Jamaica, especially in and around the Jamaica Blue Mountain coffee region and the hills of south-central Jamaica. The results also highlighted areas with limited coffee production potential across the island. This model lays the groundwork for potential applications of the model such as its use in policy making decisions and scenario planning as the industry contemplates the possible impacts of climate change on coffee growing regions across the island. This suitability model promises to be a stepping stone in the creation of novel applications of geospatial technology in agriculture within small islands. Highlights: The most suitable areas for coffee were the mountains of central and eastern Jamaica. Geology, precipitation and temperature greatly influenced coffee suitability. Model highlighted possible areas for future expansion should the need arise. Identifying best coffee growing areas should result in reduced production costs.